Histopathological Grading based on BI-RADS Mammography Category 4 and 5 in Breast Cancer - Ramadhan, Farhan Ubaidillah; Mardiyana, Lies; Kusumastuti, Etty Hary; Ghaib, Husnul (Universitas Airlangga, 2025)
Highlights: Most breast cancer patients were in the 45-49 years old age group. There was no difference in the age interval between BI-RADS C-4 and C-5 in breast cancer patients. There was no difference in histopathological grading between BI-RADS C-4 and C-5 in breast cancer patients. Abstract Introduction: Breast cancer is the most common cancer worldwide. The diagnosis of breast cancer is established by a triple diagnostic, such as clinical examination, radiology (mammography), and histopathology. This study aimed to compare mammography breast imaging-reporting and data system (BI-RADS) category 4 and 5 with histopathological grading of breast cancer at Dr. Soetomo General Academic Hospital, Surabaya. Methods: This was an observational, descriptive study with a comparative approach, utilizing secondary data from medical records of breast cancer patients at Dr. Soetomo General Hospital, Surabaya, from January 2017 to December 2021. There were 234 samples of patients who met the inclusion criteria. All statistical data were analyzed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26, with a p<0.05 regarded as statistically significant. Results: The breast cancer patients were most prevalent in the 45-49 years old age group (20.9%). The highest distribution of the BI-RADS category was C-5 (85.9). The highest distribution of histopathological grading was grade III (53%). There was no difference in age intervals between BI-RADS C-4 and BI-RADS C-5 in breast cancer patients (p=0.499). There was no difference in histopathological grading between BI-RADS C-4 and C-5 in breast cancer patients (p=0.592). Conclusion: There was no difference either in age interval or histopathological grading between BI-RADS category 4 and 5 in breast cancer patients.